Mutational analysis of the RNA-fork model of the influenza A virus vRNA promoter in vivo. - Kim, H; Fodor, E; Brownlee, G; Seong, B (1997)
The genome of influenza A virus consists of eight negative-stranded RNA segments which have partially complementary non-coding terminal sequences. Previous transcription studies of the virion RNA promoter in vitro have shown that the 5' terminus forms an integral part of the promoter and an 'RNA-fork' model has been proposed for the initiation of transcription. According to this model part of the promoter is formed by an RNA-duplex which involves complementary residues 10 to 1 2 of the 3' end and residues 11' to 13' of the 5' end. With a reverse genetics system, based on the chloramphenicol acetyltransferase (CAT) gene, we have now tested this part of the promoter in vivo. Single mutations of the conserved residues at positions 11 and 12 of the 3' terminus and at positions 12' and 13' of the 5' terminus abolished promoter activity. The introduction of complementary mutations into both termini partially restored activity. On the other hand, mutations at positions 10 of the 3' terminus and 11' of the 5' terminus inhibited activity independently of whether a base-pair was formed or not. Thus, at these positions, the nature of the residues is apparently more important than their ability to form base-pairs. These results extend our previous virion 'RNA-fork' model and are consistent with in vitro findings that the 5' terminus is involved in the initiation of transcription.